ICMI AND EDUCATION: An Effort to Prepare Muslim Intellectuals in Indonesia - Andi Tenri Yeyeng; Muhammad Saleh Tajuddin; Rohani Ab Ghani (JICSA : Journal of Islamic Civilization in Southeast Asian, 2017)
This writing explains ICMI (Ikatan Cendekiawan Muslim Indonesia) organization agenda to improve the quality Muslims intellectuals in Indonesia, particularly in educational aspect. This writing is using lybrary research to explore the role of ICMI in educational aspect in Indonesia. It is realize that there are many educational problems in Indonesia, such as teacher-oriented education, passive, less interested to get information from libraries, and not objectively oriented. The main agenda of ICMI organization in developing of Islamic education in Indonesia is that education has to be oriented to help the students to become better Muslims. Introducing modern education is very important in the improvement of the quality of human resources and people's ability to meaningfully participate in an evolving civil society in Indonesia. Moreover, education can be oriented to prepare students to have good behaviour, values, and norms, which in turn plays an important role in the improvement of the quality of civil society in Indonesia.